Rumours of “The Insurrection in Dublin” across the South Atlantic - Izarra, Laura P. Z. (ABEI Journal, 2016)
This article shows how James Stephens’ daily journalistic record of the rumours and tension of the Easter Rising in Dublin’s streets intersectswith beliefs in freedom, idealism, justice and patriotism already present in his previous work, with Roger Casement’s Speech from the Dock and narratives constructed under the Southern Cross. Based on Rosnow’s and Allport and Portsman’s concepts of rumour as well as on Igor Primoratz’s and Aleksandar Pavković’s concepts of patriotism, I deconstruct news of the Rising that reached the South Atlantic shores and spread through local and Irish community newspapers. An analysis of the words chosen by the journalists to describe the Rising – such as ‘insurrection’, ‘rebellion’, ‘revolution’, ‘rioting’, ‘rising’ – reveal the political position adopted by the newspapers of the Irish communities in Argentina and also in Brazil.Keywords: James Stephens, Easter Rising, South American press, Eamonn Bulfin, Roger Casement.